Mapping the dark matter halo of early-type galaxy NGC 2974 through orbit-based models with combined stellar and cold gas kinematics. Issue 3 (26th November 2019) - Yang, Meng; Zhu, Ling; Weijmans, Anne-Marie; van de Ven, Glenn; Boardman, Nicholas; Morganti, Raffaella; Oosterloo, Tom
ABSTRACT: We present an orbit-based method of combining stellar and cold gas kinematics to constrain the dark matter profile of early-type galaxies. We apply this method to early-type galaxy NGC 2974, using Pan-STARRS imaging and SAURON stellar kinematics to model the stellar orbits, and introducing H i kinematics from VLA observation as a tracer of the gravitational potential. The introduction of the cold gas kinematics shows a significant effect on the confidence limits of especially the dark halo properties: we exclude more than $95{{\ \rm per\ cent}}$ of models within the 1σ confidence level of Schwarzschild modelling with only stellar kinematics, and reduce the relative uncertainty of the dark matter fraction significantly to $10{{\ \rm per\ cent}}$ within 5 R e . Adopting a generalized Navarro–Frenk–White (NFW) dark matter profile, we measure a shallow cuspy inner slope of $0.6^{+0.2}_{-0.3}$ when including the cold gas kinematics in our model. We cannot constrain the inner slope with the stellar kinematics alone.